Laminitos microbiais no membro Crato (Neoaptiano), bacia do Araripe, nordeste do Brasil - Catto, Bruno [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Recent giant oil discoveries in the pre-salt sedimentary sequence of the Santos and Campos basins at southwest Brazil support a high interest in better understand carbonate rocks from the Alagoas Stage (Upper Aptian). In these offshore basins the Alagoas Stage deposits can only be investigated through indirect techniques and rock samples obtained in drilling wells. The lithological complexity and the great lateral variation in the sedimentary facies, challenge geologists and geophysics to construct accurate predictive reservoir models. Therefore, it is necessary to use analogous models at the surface to substantiate and enhance predictive subsurface models. In this sense, the Araripe Basin is notable for having large and continuous outcrops in which lacustrine carbonates are conteporaneous to Neoaptian sections. This study addresses the genesis of the carbonate facies of the Crato member, previously referred as monotonous laminated carbonates and historically interpreted as produced by chemical precipitation and/or sediment remobilization from the proximal and shallow portions of lakes. The data acquired in this study include the macroscopic outcrop and well core descriptions, associated with detailed analyses of subsurface samples. This procedure included accurate optical petrography combined with the use of scanning electron microscopy (SEM), and analytical techniques to determine the mineral and organic constituents in the carbonate facies. These new data, confirmed the pre-existence of autotrophic prokaryotes populations, such as filamentous cyanobacteria, coccoid and spyrulina, besides its organic product, the extracellular polymeric substance (EPS). The identification of calcified bacterial colonies and the organic content support the definition of the genesis and processes envolved in the generation of the carbonates. All analyzed samples revealed origin related to biologically induced and biologically influenced euhedral to...

O recente interesse por rochas carbonáticas do Andar Alagoas deve-se às grandes descobertas de petróleo no intervalo sedimentar que ficou conhecido como o pré-sal das bacias de Santos e Campos. Nestas bacias, os depósitos do Aptiano, Andar regional Alagoas, somente podem ser investigados do ponto de vista estratigráfico por técnicas indiretas e por meio de amostras obtidas na perfuração de poços. A complexidade litológica e a grande variação lateral das fácies, muitas das quais formadas por carbonatos lacustres de origem microbial, dificultam a confecção de um modelo preditivo de reservatórios. Dessa forma, faz-se necessário a utilização de modelos análogos em superfície para substanciar e aprimorar os modelos preditivos em subsuperfície. Neste sentido, a Bacia do Araripe destaca-se por possuir bons afloramentos da sucessão formada pela sedimentação de carbonatos lacustres contemporânea às seções Neoaptianas produtoras de petróleo em Santos e Campos. Dentro deste panorama, este trabalho aborda a gênese dos calcários laminados do Membro Crato. Essas fácies são historicamente interpretadas como produtos da precipitação química e processos de remobilização de finos das porções proximais e rasas dos lagos, sem qualquer citação específica sobre sua origem. Os dados utilizados neste trabalho compreendem a descrição macroscópica de afloramentos e testemunhos de poço, técnicas analíticas em amostras de subsuperfície, para determinar teor e constituinte mineral e orgânico das fácies carbonáticas, e petrografia óptica e detalhada com a utilização da microscopia eletrônica de varredura (MEV). Com base nesses novos dados foi possível determinar populações de células procariontes autotróficas, como bactérias filamentosas, cocoides e cianobactérias do gênero spirulina, além do seu principal produto orgânico, a substância polimérica extracelular (EPS - Extracellular Polymeric...
Keywords: Petrology; Geologia estratigráfica; Petrologia; Carbonatos; Geoquimica; Calcários; Bacias sedimentares; Araripe, Bacia do